STRATEGY FOR DEVELOPING PRODUCT STANDARDS, PRODUCT QUALITY, AND INNOVATION IN IMPROVING THE INTERNATIONALIZATION PERFORMANCE OF MSMES AT AIDA FURNITURE IN PASURUAN - Richa Afriana Munthe; Sudarmiatin Sudarmiatin; Imam Mukhlis (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
This research was conducted to describe how an MSME company innovates in improving its internationalization performance by developing product standards and improving product quality. The object of research is the Aida Funiture company located in Pasuruan, East Java, Indonesia. The research approach uses descriptive and qualitative methods. Data collection techniques are carried out by conducting direct interviews with business owners. The research results show that the company has a strategy related to standard product development and quality improvement. This proves that by innovating the company can compete and have a competitive advantage. Innovation is an important thing that can differentiate a product from other products so that it can improve its internationalization performance